The Olfactory Chemosensation of Hematophagous Hemipteran Insects - Liu, Feng; Chen, Zhou; Ye, Zi; Liu, Nannan (Frontiers in Physiology, 2021)
As one of the most abundant insect orders on earth, most Hemipteran insects are phytophagous, with the few hematophagous exceptions falling into two families: Cimicidae, such as bed bugs, and Reduviidae, such as kissing bugs. Many of these blood-feeding hemipteran insects are known to be realistic or potential disease vectors, presenting both physical and psychological risks for public health. Considerable researches into the interactions between hemipteran insects such as kissing bugs and bed bugs and their human hosts have revealed important information that deepens our understanding of their chemical ecology and olfactory physiology. Sensory mechanisms in the peripheral olfactory system of both insects have now been characterized, with a particular emphasis on their olfactory sensory neurons and odorant receptors. This review summarizes the findings of recent studies of both kissing bugs (including Rhodnius prolixus and Triatoma infestans) and bed bugs (Cimex lectularius), focusing on their chemical ecology and peripheral olfactory systems. Potential olfaction-based applications for the management of these Hemipteran insect vectors are also discussed.